PENGARUH MODUL EDUKASI GIZI TEMAN SEBAYA TERHADAP PENGETAHUAN DAN SIKAP REMAJA TENTANG OBESITAS DI SMAN 5 DEPOK TAHUN 2022 - Vina Vanessa (2022)
Obesity, one of the nutrition problem among adolescents, is excessive fat accumulation and increases the risk of health problems. Knowledge and attitude may play a role in the etiology of obesity among adolescents. One of the way to enhancing knowledge and attitude is education. Peer education is a part of health promotion strategy. Peer education can increase the effectiveness of the message being presented among adolescents. Peer nutrition education is expected to help adolescents better understanding the nutrition information. This study aimed to evaluate the effect of peer nutrition education using obesity module among adolescents at SMAN 5 Depok. The research method used was quasy experiment with one group pre test- post test design. Sampling was taken by simple random sampling on 50 respondents. Data analysis was using wilcoxon test. The result showed that p value on knowledge 0,000 (p <0,05) and p value on attitude 0,000 (p<0,05), it can be concluded that there is effect of peer nutrition education using module among adolescents at SMAN 5 Depok.